Proteomic analyses of the cell walls of candida albicans PGA1 and PIR32 null mutants. (c2017) - Khoury, Pamela Milad El (2017)
Though residing asymptomatically in mammalian tissues and mucosal surfaces, specific environmental cues can induce the opportunistic fungus Candida albicans to become pathogenic resulting in severe systemic and disseminated infection. The cell wall of this fungus is dynamic and its architecture is constantly modified and adapted as many virulence attributes are localized to the cell surface. Pga1 and Pir32 are two cell wall proteins that have been characterized by our lab following the generation of pga1 and pir32 null strains and comparing their respective phenotypes to the parental wild type strain. The pga1 null strain was less adherent and virulent than the wild type strain and exhibited reductions in chitin deposition, biofilm formation, filamentation, and resistance to stress. The pir32 null strain on the other hand showed more pronounced phenotypes such as hyperfilamentation ability, and increased resistance to oxidative stress in part due to a two fold increase in chitin deposition. In this study, cell wall proteomic profiles for both mutant strains were established and compared with the parental strain in order to explain the previously observed phenotypes. Major virulence proteins like Hsp70 and Mp65 were not detected in the pga1 null strain. Lipases (Lip6, 8, and 10), Sap1 and Exg2 functioning in host degradation and nutrient collection, were also undetected. Additionally, the mutant appears to lack Sod5, Erg1, Cdc11 and other proteins that have roles in cell wall integrity and resistance to environmental stress and antifungal treatment. On the other hand, key virulence factors required for proper dissemination were detected exclusively in the pir32 null strain. Such factors include the adhesin Als3, in addition to lipases, superoxide dismutases and secreted aspartyl protease family members. The mutant also appeared to be differentially expressing proteins involved in filamentous growth such as Cdc42 and Ssu81, explaining the observed hyperfilamentous phenotype. As such, cell wall proteomic analysis is a powerful tool that allowed us to identify key virulence traits responsible for the observed phenotypes of the mutant strains.